Milo stover and forage sorghum silages for growing heifers - K. Bolsen; L. Corah; C. Grimes; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1976)
Ninety-six heifer calves were used to compare four silage combinations: (1) 100% milo stover, (2) 67% milo stover and 33% forage sorghum, (3) 33% milo stover and 67% forage sorghum and (4) 100% forage sorghum. Each ration was fed to four pens of six heifers each during the 88-day trial. Heifers fed 100% forage sorghum made the fastest and most efficient gains(P<.05); those fed 100% milo stover, the slowest and least efficient gains (P<.05). Based on gains obtained from these two rations, the 67% milo stover silage ration produced 16% faster gain than predicted; the 33% milo stover ration, a 5% faster gain than predicted.
Keywords: Cattlemen& #x27; s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Milo stover silage; Forage sorghum silage; Heifers